Culture, Music Education, and the Chinese Dream in Mainland China - Ho, Wai-Chung (Cultural Studies and Transdisciplinarity in Education,, 2018)
This book focuses on the rapidly changing sociology of music as manifested in Chinese society and Chinese education. It examines how social changes and cultural politics affect how music is currently being used in connection with the Chinese dream. While there is a growing trend toward incorporating the Chinese dream into school education and higher education, there has been no scholarly discussion to date. The combination of cultural politics, transformed authority relations, and officially approved songs can provide us with an understanding of the official content on the Chinese dream that is conveyed in today's Chinese society, and how these factors have influenced the renewal of values-based education and practices in school music education in China. Ambitious in scope, the book explores the socio-historical and political complexities underpinning music education in mainland China. Based upon an impressive mix of scholarly literature, official documents, text books and interviews with music teachers in Beijing, it represents a major contribution to the field of international and comparative research in music education. Dr. Gordon Cox, Co-Editor (with Robin Stevens), The Origins and Foundations of Music Education: International Perspectives (London and New York: Bloomsbury, 2017). It is rare to come across research and scholarship in music education with so wide a vision and so acute a political sensibility as this book. Wai-Chung Ho, already internationally renowned as an expert on Chinese music education, has excelled herself in this masterful analysis. The book will be of interest not only to specialists in the field of Chinese music education itself, but to anyone concerned about relationships between music, society, policy and education across a range of contexts. Professor Lucy Green, Emerita Professor of Music Education, UCL Institute of Education, University College of London, UK Understanding of the relationship between the Chinese Dream, soft power and the deployment of culture, in particular music, in community and school music education in China to reconstruct China as a nation is of the utmost importance at this time. Professor Ruth Wright, Music Education, Don Wright Faculty of Music, Western University Canada, Canada.